Effectivity of Virtual Reality-Based Media on Elementary School Students' Spatial Skills in Mathematics Learning - Nuramalia Hidayati; Andika Arisetyawan; Andhin Dyas Fitriani (Jurnal Profesi Guru Indonesia, 2026)
Developing geometry-related spatial abilities in primary education is critical to fostering mathematical reasoning and advanced abstract problem-solving skills. Traditional elementary geometry instruction heavily relies on static 2D illustrations, which fail to cultivate structural spatial imagination, yet empirical investigations into how immersive Virtual Reality (VR) environments mathematically reshape three-dimensional cognitive mapping in young learners remain insufficient. This study aims to examine the effect of virtual reality-based media on the spatial abilities of elementary school students in mathematics learning. [Method] Utilizing a quantitative quasi-experimental framework, this study involved 44 fifth-grade students, systematically partitioned into an experimental cohort (n = 22, integrated with VR-based media) and a control cohort (n = 22, utilizing conventional methods). Data were gathered through a validated mathematical spatial ability test and analyzed using descriptive metrics (mean, standard deviation, and learning completeness percentages) in conjunction with paired and independent sample t-tests. The empirical findings demonstrate that VR-based media exerts a profoundly positive and statistically significant effect on students' spatial abilities. The experimental group achieved a vastly superior post-test mean score (90.19) compared to the control group (71.04). Additionally, a tighter standard deviation in the experimental class revealed a more equitable distribution of skill mastery, while their learning completeness percentage reached a staggering 92.37% against the control group's mere 72.63% (p < 0.05). Consequently, VR-based media serves as a potent and transformative pedagogical alternative to address deficits in elementary students' spatial-mathematical capacities. Beyond localized score gains, these insights offer a scalable framework for educational designers to deploy immersive technologies that convert abstract, multi-dimensional mathematical concepts into tangible, concrete learning experiences.